Strategi Parenting untuk Menghadapi Tantangan di Era Digital - Elfira, Ninil; Niki Kusaini, Utami; Yulianti, Yulianti (Faculty of teaching training and education, 2025)
This research aims to find out parenting strategies in assisting children in the digital era. Given the current technological developments, parents face new challenges in understanding and controlling how their children interact with the vast and rapid flow of information. The goal of these strategies is to prevent children from becoming addicted to gadgets and being exposed to negative content that could adversely affect their character. Important steps that must be taken include limiting gadget usage time, monitoring the content accessed, and maintaining open communication about technology. Thus, parents play a crucial role in shaping a safe and responsible attitude towards technology in their children, enabling them to progress into intelligent and wise individuals in using digital media. The research method used is qualitative, employing literature review or bibliographic study. The sources referenced include journals, books, and scientific articles. This method provides a solid theoretical foundation for determining parenting strategies in facing challenges in the digital era.